2023
DOI: 10.3390/agronomy13041070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilization and Soil Water Content on Seed and Oil Yield in Perennial Castor in a Mediterranean Environment

Abstract: Castor (Ricinus communis L.) is an oilseed species that can be grown as a semi-perennial in Mediterranean environments, including the coastal areas of Sicily. The present study investigated the optimization of cultivation techniques for castor, with the crop being maintained over a two-year period, through the evaluation of different agronomical inputs in order to increase seed yield. The effects of irrigation (I) and nitrogen fertilization (N) on the seed and oil yield and their components were assessed in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
3
0
0
Order By: Relevance
“…These results confirmed what was found for our 'C856', which averaged, independently of the sowing date, about 50%. Nevertheless, our results are perfectly in line with those reported in the literature for the oil content, ranging from 49.0-53.0% in dwarf hybrids [39] from 30.4 to 50.6% (in 'Local' genotype) [30], from 40.1 and 57.4% [40], and from 24.2 to 50.0% in dwarf and normal castor [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results confirmed what was found for our 'C856', which averaged, independently of the sowing date, about 50%. Nevertheless, our results are perfectly in line with those reported in the literature for the oil content, ranging from 49.0-53.0% in dwarf hybrids [39] from 30.4 to 50.6% (in 'Local' genotype) [30], from 40.1 and 57.4% [40], and from 24.2 to 50.0% in dwarf and normal castor [41].…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirmed other studies in the Mediterranean area. Indeed, Calcagno et al (2023) [30] found that, in castor sown late in April, the ripening was reached in just 145 days in a local variety, in line with our 'Local' genotype, which took between 156 and 135 days for the E-M cycle in spring sowings. Whereas, Patanè et al (2019) [31] found that 99 days are sufficient with sowings in May, matching the time that occurred in the late sowings of our 'Local' genotype, which needed 111 and 94 days (SW3 and SW4, respectively).…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the effect of nitrogen fertilization, there was an increase in castor seed yield in the treatment supplied with 120 kg N ha −1 , as also reported by Pari et al (2022), who obtained similar results for castor hybrids under a Mediterranean climate with high‐input field management (100 kg N ha −1 ) and Calcagno et al (2023), who investigated the perennial habit of castor under different irrigation and nitrogen fertilization levels in the Mediterranean area while maintaining the crop over a 2‐year period. Weiss (2000) reported that nitrogen fertilization had little effect on seed oil content, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 84%